1983
DOI: 10.1007/bf02307013
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural alterations in rat and cat retina and pigment epithelium induced by chloroquine

Abstract: Chloroquine retinopathy in rats and cats was studied (in long-term experiments on rats the drug was injected into the stomach). We observed the slow development of the pathological process, accompanied by the appearance of membrane inclusions in GC, structural alterations in the RPE, and after 10 months complete destruction of the outer segments of the photoreceptors. In experiments on cats, after a single intravitreous chloroquine injection destruction of the photoreceptors, similar to that observed in rats, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
3

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 15 publications
3
30
0
3
Order By: Relevance
“…Electron microscopy showed that mor phology of rat retina in rats receiving peroral chloroquine during 11 months was analo gous to that observed previously [6]. There was no difference in distribution of inclu sions in the group of rats receiving chloro quine with ionol.…”
Section: Ratssupporting
confidence: 53%
“…Electron microscopy showed that mor phology of rat retina in rats receiving peroral chloroquine during 11 months was analo gous to that observed previously [6]. There was no difference in distribution of inclu sions in the group of rats receiving chloro quine with ionol.…”
Section: Ratssupporting
confidence: 53%
“…This is supported by the fact that retinopathy can be reproduced equally both in albino and in pigmented rabbits, rats and cats [21][22][23][24][25]. Several histopathologic investigations report retinal changes, which showed membranous cytoplasmic bodies predominantly in the ganglion cells of the retina in man [26], monkey [27] and rodents [28], whereas the pigment epithelium was affected only in very advanced retinopathy.…”
Section: Introductionmentioning
confidence: 56%
“…While early studies assumed a binding of chloroquine to melanin to cause retinal toxicity [18,19], it is nowadays known that melanin is not the primary mechanism of ocular toxicity [20][21][22][23][24][25]. Histopathologic investigations showed membranous cytoplasmic bodies predominantly in the ganglion cells of the retina in both man [26], monkey [27] and rodents [28], whereas the pigment epithelium showed only changes in very advanced retinopathy.…”
Section: Toxicitymentioning
confidence: 99%
“…Three pathogenic mechanisms are supposed to play a role in this process: (1) Chloroquine as a cationic amphiphilic drug diffuses into lysosomes, where it inhibits lysosomal enzymes and therefore prevents regular digestion of auto-and heterophagocytic material [1] . (2) Chloroquine accumulates in the retinal pigment epithelium (RPE) and the choroid, binding to melanin [2] . (3) Chloroquine treatment induces oxidative stress: it was found that glutathione (GSH) is reduced and lipid peroxidation increased during chloroquine treatment [3] .…”
Section: Introductionmentioning
confidence: 99%